Do Parties Punish MPs for Voting Against the Party Line? - Björn Kauder; Niklas Potrafke; Marina Riem (Center for Economic Studies and ifo Institute (CESifo), 2017)
We examine whether parties punish politicians who vote against the party line in roll-call votes. Using data of German members of parliament over the legislative period 2009-2013, we take into account that the effect of punishment differs along the list of candidates because a candidate is punished more when he loses positions at the threshold of promising list positions. The dataset includes the voting behavior of 257 MPs in 218 roll-call votes. Our results do not show that parties account for the voting behavior by punishing politicians who have voted against the party line. Political parties may attract different groups of voters by tolerating politicians who vote according to their own credo. Qualities other than the voting behavior seem to matter to political parties when nominating candidates.
Keywords: D72; D78; P16; 330; voting against the party line; adherence to the party line; roll-call votes; proportional representation; party lists; selectorate